2014
DOI: 10.1680/geot.13.t.016
|View full text |Cite
|
Sign up to set email alerts
|

On the reliability of 3D numerical analyses on passive piles used for slope stabilisation in frictional soils

Abstract: The use of passive piles can be an effective method for stabilising unstable slopes. Unfortunately, no rigorous analytical solution has so far been proposed for assessing the ultimate, lateral pile–soil pressure distribution under drained conditions for the design of passive piles in a slope. The present work focuses on the reliability of a finite-element model (FEM) used to assess the ultimate limit state conditions of passive piles in frictional soils. The paper also provides an estimate of the ultimate load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…Both the anchored wall and the diaphragm wall were assumed to be perfectly elastic, as in Kourkoulis et al (2011) and Muraro et al (2014), who showed the negligible effects of a large decrease in elastic stiffness and Poisson ratio of the retaining structure (a pile in their case) on the ultimate load.…”
Section: Finite-element Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the anchored wall and the diaphragm wall were assumed to be perfectly elastic, as in Kourkoulis et al (2011) and Muraro et al (2014), who showed the negligible effects of a large decrease in elastic stiffness and Poisson ratio of the retaining structure (a pile in their case) on the ultimate load.…”
Section: Finite-element Modelsmentioning
confidence: 99%
“…They found the simple Mohr-Coulomb constitutive model sufficiently accurate for modelling interface behaviour. The friction at the slip surface interface was initially assumed to equate to the soil friction angle (μ ¼ ϕ), in order to generate the initial stress condition (as in Muraro et al, 2014), then μ was reduced to a value slightly higher than the slope's inclination (μ ¼ α þ 0·001°) to simulate a condition nearing collapse due to the presence of a thin weak layer. The soil-wall friction angle was assumed positive for downward-tilting soil pressure ( Fig.…”
Section: Finite-element Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7 is a sketch of the failure mechanisms with associated patterns of soil reaction and internal forces along the pile. From equilibrium considerations, as already shown by Muraro et al (2014) dimensionless shear force and bending moment at the interface for mechanisms A and C are obtained as Mode A Fig. 5.…”
Section: Ultimate Pile Load In Drained Conditionsmentioning
confidence: 87%
“…The latter provided solutions for a single free-head pile embedded in fine-grained soil in undrained conditions (total stress analysis) in the framework of the limit equilibrium method. With a similar approach, Muraro et al (2014) have obtained the solution for the case of a rigid (not yielding) single free-head pile in drained conditions. Ito & Matsui (1975) studied the pile reaction forces when the soil is forced to squeeze between two infinitely long piles, providing two expressions obtained by using either the theory of plastic deformation or the theory of plastic flow.…”
Section: Introductionmentioning
confidence: 99%